Electrogenic Sulfur Oxidation by Cable Bacteria in Bivalve Reef Sediments - Malkin, Sairah Y.; Seitaj, Dorina; Burdorf, Laurine D. W.; Nieuwhof, Sil; Hidalgo-Martinez, Silvia; Tramper, Anton; Geeraert, Naomi; De Stigter, Henko; Meysman, Filip J. R. (Frontiers in Marine Science, 2017)
Cable bacteria induce long-distance electron transport in the seafloor and can exert a powerful control on the elemental cycling in marine sediments by creating extreme excursions in porewater pH. Yet, the natural distribution of cable bacteria is still largely unknown, and so their role in coastal biogeochemical cycling remains poorly quantified. Here we show that cable bacteria can be abundant in the sediments of intertidal bivalve reefs, where they strongly influence the pore water geochemistry, resulting in a potentially beneficial interaction between the sulfur oxidizing microbes and biodepositing fauna. Cable bacteria occurred in sediments accumulating within mussel and oyster reefs in the Wadden Sea (The Netherlands), at cumulative filament densities up to 1038 m cm-2. Additionally, cable bacteria were found at moderately high cumulative filament densities (up to 56 m cm-2) in a heavily bioturbated sandy sediment adjacent to the muddy reefs. Microsensor profiling revealed strong sulfide removal and intense acid generation associated with the electrogenic sulfide oxidation metabolism of the cable bacteria. Strongly elevated concentrations of dissolved calcium (up to 35 mM), manganese (up to 250 µM), and iron (up to 700 µM) were observed in the pore waters, consistent with acidity-driven dissolution of calcium carbonates and iron sulfides. This field study provides substantive evidence that cable bacteria exert a decisive control on the cycling of sulfur and carbonate minerals in cohesive coastal sediments, and identifies that the distribution and influence of cable bacteria covers a greater range of natural habitats than previously believed.